Dietary patterns and risk of dementia: the Three-City cohort study - Barberger-Gateau, P; Raffaitin, C; Letenneur, L; Berr, C; Tzourio, C; Dartigues, J F; Alpérovitch, A (Neurology, 2007)
Dietary fatty acids and antioxidants may contribute to decrease dementia risk, but epidemiologic data remain controversial. The aim of our study was to analyze the relationship between dietary patterns and risk of dementia or Alzheimer disease (AD), adjusting for sociodemographic and vascular risk factors, and taking into account the ApoE genotype. A total of 8,085 nondemented participants aged 65 and over were included in the Three-City cohort study in Bordeaux, Dijon, and Montpellier (France) in 1999-2000 and had at least one re-examination over 4 years (rate of follow-up 89.1%). An independent committee of neurologists validated 281 incident cases of dementia (including 183 AD). Daily consumption of fruits and vegetables was associated with a decreased risk of all cause dementia (hazard ratio [HR] 0.72, 95% CI 0.53 to 0.97) in fully adjusted models. Weekly consumption of fish was associated with a reduced risk of AD (HR 0.65, 95% CI 0.43 to 0.994) and all cause dementia but only among ApoE epsilon 4 noncarriers (HR 0.60, 95% CI 0.40 to 0.90). Regular use of omega-3 rich oils was associated with a decreased risk of borderline significance for all cause dementia (HR 0.46, 95% CI 0.19 to 1.11). Regular consumption of omega-6 rich oils not compensated by consumption of omega-3 rich oils or fish was associated with an increased risk of dementia (HR 2.12, 95% CI 1.30 to 3.46) among ApoE epsilon 4 noncarriers. Frequent consumption of fruits and vegetables, fish, and omega-3 rich oils may decrease the risk of dementia and Alzheimer disease, especially among ApoE epsilon 4 noncarriers.